Effect of geometrical properties of finger joint on the bending strength of timber (profile ii) / Mohd Allias Mohd Hasseri - Mohd Hasseri, Mohd Allias (2002)
Nowadays, finger jointed woods are widely used in wood industry as a joinery and also in structural members. The most important criteria in designing the timber structures are its bending strength. A study was conducted to determine the effect of finger joint profile on the bending strength of finger-jointed woods. This study was carried out by using Light Red Meranti wood. In this study case, three different profiles are used where ten samples for each profiles are prepared and tested. Twenty control samples were also needed to be prepared and tested for comparison. The samples also tested for their modulus of elasticity (MOR) besides bending strength. The dimensions of the samples used are 20 x 43 x 400 mm and this is standard for all the samples. This study is to investigate the bending strength of different finger joint profiles and the control sample. Thus, the relationship between profile geometry and the strength can be obtained and also, to determine the modulus of elasticity where it is the important properties in design timber as structural member. It was found from the study that the maximum value of mean modulus of elasticity for the finger joint profiles (average of all the profiles) is 9853.56 N/mm while for the control sample is 9666.51 N/mm2. For the bending strength, the maximum mean value (average of all the profiles) is 39.72 N/mm‘ and for the control sample is 57.80 N/mm .